Retained Fractured Intravenous Catheter: A Report of Two Cases - Onyinyechukwu Adaeze Arua; Akanni Abdulazeez Bolaji; Ubanatu Promise; Chidiebere Peter Echieh (Nigerian Journal of Medicine, 2024)
Retention of fractured intravenous (IV) catheters is an uncommon but significant complication arising from the prolonged use of peripheral IV cannulas. This report details two cases involving young women. The first case features a 23-year-old postmyomectomy patient who presented to the emergency unit after a fractured IV cannula was discovered during its removal at a peripheral center two days earlier. Doppler ultrasonography revealed that the fractured catheter was still lodged in the left cubital vein, leading to its surgical removal under local anesthesia. The patient recovered well and was discharged the following day. The second case involves a 32-year-old woman who was referred to the cardiothoracic unit due to puerperal sepsis. An 18G catheter in the left cephalic vein fractured, leaving the tip retained after five days of use. Doppler ultrasonography again assisted in localization, and venotomy was performed to extract the retained portion. Notably, both catheters were found at their original insertion sites, with no signs of migration despite the delay in treatment. These cases highlight that while the retention of fractured IV cannulas is rare, it can still occur, especially with prolonged use. Prompt intervention is crucial to avoid complications such as migration toward the heart and associated sequelae. Inflammation and thrombosis may mitigate this risk, as seen in the patients. Surgical retrieval was deemed effective and cost-efficient in both instances. This underscores the need for improved oversight of medical materials to discourage prolonged IV catheter use.